Effectiveness of Murabaha Financing Dispute Settlement Through Mediation at Indonesian Islamic Banks - Dea Safilah; Moch. Syafii; Syahril Syahril (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This study assesses the effectiveness of mediation in murabahah funding dispute resolution at Bank Syariah Indonesia KC Asia Afrika Bandung City. This study aims to discover and comprehend how Indonesian Islamic Banks manage contentious disputes, with an emphasis on murabahah financing, as well as the effectiveness of murabahah financing dispute resolution through mediation at Indonesian Islamic Banks. The employed research method is qualitative research with a qualitative descriptive approach that depicts a scenario in the agency and community through observation, interviews, and recording. The primary source of data for this study is the results of interviews with the Bank and its customers. While secondary sources are collected from library sources such as books, journals, and other relevant library materials to the topic of research. According to the findings of the study, Bank Syariah Indonesia's strategies for resolving non-performing financing for clients with murabahah financing disputes are simple and clear. The effectiveness of the resolution of murabahah funds through mediation is believed to be effective because it may be measured by the Bank's success in carrying out its mediation-related tasks. A proportion between 80% and 90% would be adequate for the effectiveness of murabahah financial dispute resolution.